Body Composition and Level of Physical Activity in Post-COVID-19 Patients - , Wendell Costa Bila; , Andresa Machado e Silva; , Leonardo Gomides Bicalho; , Ronilson Cândido; , Jeniffer Rafaela Silva Costa; , José Vitor Vieira Salgado; , Cezenário Gonçalves Campos; , Ana Carolina Corrêa Café; , Priscila Cristian do Amaral; , Rommel Larcher Rachid Novais; , Joel Alves Lamounier; , Eduardo Sérgio da Silva (Archives of Current Research International, 2023)
Introduction: The coronavirus disease 2019 (COVID-19) pandemic has created a public health crisis. Body composition is an important nutritional indicator, knowledge of which allows the subdivision of body weight into some components, mainly lean mass or fat-free mass and body fat mass of individuals. Aim: To evaluate lean mass and body fat in post-COVID-19 patients, correlating them with length of stay, pre-hospitalization and post-hospitalization and patients' level of physical activity, specifying relative segmental fat. Methodology: Observational, cross-sectional study, with quantitative analysis, with a convenience sample, approved by the Research Ethics Committee of the State University of Minas Gerais. Patients undergoing care/rehabilitation in the physiotherapy/outpatient sector at a Regional Rehabilitation Center, with a history of diagnosis of COVID-19, aged 20 years or over, of both sexes, were invited to participate in the research. Lean body mass (LBM) and body fat (BF) were obtained by evaluating horizontal tetrapolar electrical bioimpedance (BIA). Body fat segmentation was collected by measuring skinfold thickness. Physical activity level (PAL) was obtained using the International Physical Activity Questionnaire (IPAQ). The hospitalization history was obtained by filling out the registration form. Results: Data from 20 patients were analyzed. The average LBM found was 69.7% and 30.3% of BF. There was no correlation between sedentary lifestyle and LBM. 50% of patients had previous comorbidities and 50% had a mild form of COVID-19 infection. 10% required hospitalization and ventilator support. 85% were physically active or very active. There was a greater presence of body fat in the abdominal and suprailiac region. Conclusion: LBM proved to be superior to other studies carried out and no statistically significant correlation was found between LBM and history of hospitalization, time elapsed since illness and PAL. The regions with the greatest share of body fat were abdominal and suprailiac, important for inflammatory reasons and risk factors for various diseases, especially cardiovascular diseases.